Update on Low-Molecular Weight Hyaluronic Acid in Dermatology: A Scoping Review - Stephanie Waggett; Elliott Lyles; Todd Schlesinger (European Medical Journal Dermatology)
Introduction: Hyaluronan, or hyaluronic acid (HA), is a naturally occurring glycosaminoglycan present in the skin, joints, and eyes that provides hydration, lubrication, protection, and other important benefits. HA in dermatology is commonly discussed in the context of its anti-ageing properties. However, both pre-clinical and clinical studies have shown numerous applications of HA, low-molecular-weight (LMW) HA, and hybrid LMW/high-molecular-weight HA in dermatology. LMW-HA exhibits antioxidant, anti-tumour, and angiogenic properties, and given its size, an ability to fully penetrate the skin. Aims: The purpose of this review was to explore the current science and utility of LMW-HA in clinical dermatology and provide an update on its use. Methods: A PubMed search from 2003–2023 on LMW-HA was conducted to evaluate LMW-HA’s utility in clinical dermatology. Results: Identified applications of LMW-HA in medical dermatology included treatment of acute and chronic wounds, rosacea, scars, and seborrhoeic dermatitis. Cosmetic applications of LMW and hybrid HA included treatment of skin ageing, enlarged pores, and skin laxity, as well as enhancement of skin hydration. Topical LMW-HA administration promoted healing after cosmetic procedures, chemical peels, and ingrown toenail surgery. Studies of topical and oral LMW-HA demonstrated adequate safety, and newer techniques of administration, such as needleless jet injection, are available. Conclusion: Exploration and understanding of the properties and benefits of LMW-HA are key to translating its usage in the clinical setting. Basic scientists and dermatologists have achieved substantial progress over the past two decades, and several applications of LMW-HA in dermatology were identified. Additional advantages of LMW-HA are worth exploring.